Los SWAP versus los programas y proyectos. ¿Una coexistencia pacífica? - Gómez Galán, Manuel (Revista Española de Desarrollo y Cooperación, 2023)
In this article, the author reflects on two instruments of development aid: the Sector Wide Approaches, and the programs and projects used by Spanish Cooperation; showing off their strengths and weaknesses in some key aspects.